Perencanaan Strategis Pengelolaan Sumberdaya Pesisir Terpadu di Kelurahan Pulau Panggang Kecamatan Seribu Utara, Kabupaten Kepulauan Seribu Provinsi DKI Jakarta - Siti Amanah (Buletin Ekonomi Perikanan, 2004)
Integrated coastal management is aimed at coping and preventing resources destruction, assuring coordination amongst institutions involved at the resource exploitation and improving the quality human life. However, that approach can not be carried out without a well vision, clear missions and goals, and program establishment that take into account of the stakeholders interests and needs. Thousand islands as part of Jakarta region have been experienced over exploitation and too many stakeholders take benefits from the resources. Therefore, a well strategic planning to manage the resources is needed to ensure the resources sustainability as well as the welfare of the community.